Advances of bioethanol production using ionic liquids - Elgharbawy, Amal A.M.; Azmi, Nor Azrini Nadiha; Moniruzzaman, Muhammad (CRC Press, 2023)
Ionic liquids (ILs) have been utilized significantly for biomass, particularly, lignocellulosic biomass processing which transforms eventually to bioenergy. ILs are getting more attention as they are environmental-friendly and can be designed for specific applications. To affordably manufacture high-grade biofuels and high-end biochemicals, appropriate pretreatment technologies are necessary for the breakdown of the complex biomass structure. Because of their emission profile, recyclability, low vapor pressure, and tunable features, ILs offer a lot of promise for energy-efficient biomass pretreatment where certain ILs can even be made from sustainable biomass feedstocks. However, a few issues are currently impeding the large-scale adoption of ILs, including the lack of detailed understanding of degradation and their high cost of production, which hinders process optimization. Despite these challenges, recent advances have been made to further investigate ILs as potential solvents for biomass processing and bioethanol production, and this chapter presents the latest progress in ILs-assisted bioethanol production from lignocellulosic biomass.